MENGATASI KEAMANAN DI DALAM SQL INJECTION DAN CARA PENCEGAHANNYA - M Andika Saputra; Hyoga Hara Kusuma; Ali Ibrahim (Annual Research Seminar (ARS), 2017)
ABSTRACTSecurity is one important factor that help in development website. With a number of service business web-based like shop online and forth, so security stored data need to take care of well. Of the nature of application that often many accessed by easy by anyone can give its own problems because the application could cause attack security. One form of attack security on the application web namely sql injection. SQL Injection is the type action hackingon the security of the computer on which an attacher could get access to the base of data in system. A method of SQL Injection used by hackers usually use form-form in of website which not furnished with script special security.